A Flexible Photovoltaic Fatigue Factor for Quantification of Mechanical Device Performance - Sun, Lulu; Fukuda, Kenjiro; Guo, Ruiqi; Castriotta, Luigi A.; Forberich, Karen; Zhou, Yinhua; Someya, Takao; Brabec, Christoph J.; Almora, Osbel (Advanced Functional Materials, 2025)
Flexible emerging photovoltaic technologies, such as organic and perovskite photovoltaics, hold great potential for integration into tents, wearable electronics, and other portable applications. Recently, Fukuda et al. (2024) propose a bending test protocol for standardizing the mechanical performance characterization of flexible solar cells, focusing on 1% strain over 1 000 bending cycles. This marked an important step toward establishing consistency and good practices in the literature. However, even with this unified protocol, accurately comparing the mechanical flexibility of solar cells is hindered by the variated influence of parameters like thickness, bending radius, and power conversion efficiency (PCE) evolution during mechanical testing. Herein, a new figure of merit is introduced, the flexible photovoltaic fatigue factor (F), which integrates PCE retention, strain, and bending cycles into a cohesive framework. Guided by a detailed multilayer mechanical model, this metric enables more accurate strain analysis and promotes consistent reporting, paving the way for performance optimization in flexible photovoltaics.
CRIS-Team Scopus Importer:2025-01-31
Keywords: bending test; flexible solar cells; mechanical stability; mechanical strain; operational photovoltaic stability